Teacher Appraisal Systems of Critical Incidents Experienced in Iranian EFL Classroom Context - Husain Abdulhay (Yayasan Visi Intan Permata, 2023)
This study sought to solicit, through the Geneva Appraisal Questionnaire (GAQ), Iranian EFL teachers’ emotional experiences and their ensuing control and authority practices. In so doing, a total of forty university instructors in Iran were recruited to participate in the study by filling in the instruments, of which thirteen were returned back. The content analysis of the data was quantitatively and qualitatively done to pinpoint the frequency of the occurrences of the emotional events and to scour the teachers’ feelings, behaviors, and reactions to the encountered situations. The data gleaned from both female and male teachers in this study disclosed the recalling of the negative events more than the positive ones. The teachers’ reservations and expectations and the lack of dexterity to confront the unprecedented behaviors were witnessed to be the main causes of experiencing negative emotions. However, the teachers’ commiseration and empathetic teaching styles were reported as the reasons for their experiences of positive feelings. The results of this study may have some practical implications and suggestions for language teacher education.